2020
DOI: 10.1073/pnas.2015919117
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular cyclic dinucleotides induce polarized responses in barrier epithelial cells by adenosine signaling

Abstract: Cyclic dinucleotides (CDNs) are secondary messengers used by prokaryotic and eukaryotic cells. In mammalian cells, cytosolic CDNs bind STING (stimulator of IFN gene), resulting in the production of type I IFN. Extracellular CDNs can enter the cytosol through several pathways but how CDNs work from outside eukaryotic cells remains poorly understood. Here, we elucidate a mechanism of action on intestinal epithelial cells for extracellular CDNs. We found that CDNs containing adenosine induced a robust CFTR-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…H151, a specific inhibitor for STING and RU.521, a specific inhibitor for cGAS were added 1 h previous infection of THP-1 cells at 10 μM and 10 μg/ml, respectively, selected according to the previously published results ( Chang et al., 2020 ; Hayden et al., 2020 ). Then, cells were infected with rNiV-eGFP or rMeV-edmH-eGFP and incubated for 24 or 48 h at 37°C with 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…H151, a specific inhibitor for STING and RU.521, a specific inhibitor for cGAS were added 1 h previous infection of THP-1 cells at 10 μM and 10 μg/ml, respectively, selected according to the previously published results ( Chang et al., 2020 ; Hayden et al., 2020 ). Then, cells were infected with rNiV-eGFP or rMeV-edmH-eGFP and incubated for 24 or 48 h at 37°C with 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…We profiled the expression levels of the proteomes in c-di-AMP and c-di-GMP treated HGFs. While c-di-AMP and c-di-GMP are negatively charged and hence difficult to get into cells, earlier studies by us and also by others have shown that at high enough concentrations (such as 100 µM) some of the CDN get into the cell to affect the signaling pathway [ 14 , 15 , 23 ]. We also chose a 24 h time period for cell exposure to CDNs to mimic chronic infection whereby mammalian cells are constantly exposed to bacterial PAMPs for extended period.…”
Section: Resultsmentioning
confidence: 99%
“…One reason for the preferential localization of CD73 in villus tip enterocytes is to counteract the ATP released by bacteria in the intestinal lumen and thereby control inappropriate immune activation by the host microbiome. Other potential functions may include the metabolism of cyclic dinucleotides to regulate host defense mechanisms at mucosal surfaces, and CD73 may also serve as a source of antimicrobial adenosine to prevent bacterial colonization and infection [68]. CD73 distribution on pericentral hepatocytes in the mammalian liver likely enables the cells to calibrate their metabolic activities under physiological low-oxygen conditions because genetic deletion of hepatocyte CD73 results in metabolic and inflammatory liver injury [29].…”
Section: Cd73 Is Zonally Expressed On Subsets Of Cells Within Epithelial Tissuesmentioning
confidence: 99%